2016
DOI: 10.1093/nar/gkw467
|View full text |Cite
|
Sign up to set email alerts
|

Human mutations affect the epigenetic/bookmarking function of HNF1B

Abstract: Bookmarking factors are transcriptional regulators involved in the mitotic transmission of epigenetic information via their ability to remain associated with mitotic chromatin. The mechanisms through which bookmarking factors bind to mitotic chromatin remain poorly understood. HNF1β is a bookmarking transcription factor that is frequently mutated in patients suffering from renal multicystic dysplasia and diabetes. Here, we show that HNF1β bookmarking activity is impaired by naturally occurring mutations found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 40 publications
7
55
0
Order By: Relevance
“…However, several studies reported unclear (Caravaca et al 2013) or false negative results (Chen et al 2002;Blobel et al 2009;Mishra et al 2009;Wu et al 2015) when using immunofluorescence to assess MCB, which was suggested to be due to limited accessibility of epitopes to antibodies within the dense mitotic environment (Chen et al 2002;Kadauke and Blobel 2013;Wu et al 2015) but also formaldehyde fixation artifacts (Pallier et al 2003;Kumar et al 2008). Similar to previous reports on other transcription factors binding to mitotic chromosomes (Pallier et al 2003;Kumar et al 2008;Lerner et al 2016), we were unable to observe mitotic chromosome localization of SOX2 and OCT4 after formaldehyde fixation (data not shown). However, using a mixture of 95% methanol and 5% acetic acid previously shown to preserve the localization of transcription factors bound to mitotic chromosomes (Kumar et al 2008), we could observe MCB of endogenous SOX2 and OCT4 by immunofluorescence.…”
Section: Discussionsupporting
confidence: 91%
“…However, several studies reported unclear (Caravaca et al 2013) or false negative results (Chen et al 2002;Blobel et al 2009;Mishra et al 2009;Wu et al 2015) when using immunofluorescence to assess MCB, which was suggested to be due to limited accessibility of epitopes to antibodies within the dense mitotic environment (Chen et al 2002;Kadauke and Blobel 2013;Wu et al 2015) but also formaldehyde fixation artifacts (Pallier et al 2003;Kumar et al 2008). Similar to previous reports on other transcription factors binding to mitotic chromosomes (Pallier et al 2003;Kumar et al 2008;Lerner et al 2016), we were unable to observe mitotic chromosome localization of SOX2 and OCT4 after formaldehyde fixation (data not shown). However, using a mixture of 95% methanol and 5% acetic acid previously shown to preserve the localization of transcription factors bound to mitotic chromosomes (Kumar et al 2008), we could observe MCB of endogenous SOX2 and OCT4 by immunofluorescence.…”
Section: Discussionsupporting
confidence: 91%
“…2Y,Z). We thus conclude that detection of RNAP2 in mitotic chromatin is both antibody dependent and that cases of exclusion are likely due to fixation artifacts, as previously reported for transcription factors (Lerner et al 2016;Teves et al 2016). Importantly, the presence of an active form of RNAP2 in mitosis has been reported at the centromere (Liu et al 2015), but our observation agrees with various hints throughout the literature that it is also present at low levels throughout mitotic chromatin.…”
Section: Rna Pol II During Mitosissupporting
confidence: 91%
“…These results suggest that low levels of transcribing RNAP2 are present, and that only when elongation is blocked and there is a backup of RNAP2 at the promoter is the signal detected. In addition, recent studies have shown that formaldehyde cross-linking artifactually removes proteins from mitotic chromatin (Lerner et al 2016;Teves et al 2016). Even though transcription factors were visibly excluded from mitotic chromatin by immunofluorescence (IF), fluorescently labeled fusions of the same proteins colocalized with mitotic chromatin in live cells.…”
mentioning
confidence: 99%
“…In 2003, our group identified the osteogenic master regulator RUNX2 as the first sequence specific bookmark that remained associated with target genes through mitosis (Zaidi et al 2003). Subsequent studies of RUNX family of phenotypic transcription factors from our group (Zaidi et al 2003;Young et al 2007a;Young et al 2007b;Ali et al 2008;Bakshi et al 2008;Pande et al 2009;Ali et al 2010;Zaidi et al 2010;Ali et al 2012;Zaidi et al 2014;Lopez-Camacho et al 2014) and studies by other groups examining various transcription factors (Xing 2005;Sarge and Park-Sarge 2005;Dey et al 2009;Blobel et al 2009;Zhao et al 2011;Kadauke et al 2012;Arampatzi et al 2013;Caravaca et al 2013;Kadauke and Blobel 2013;Lake et al 2014;Zaret 2014;Lodhi et al 2014;Wong et al 2014;Lodhi et al 2016;Lerner et al 2016;Festuccia et al 2016) have identified mitotic bookmarking as a key epigenetic mechanism for regulation of genes that coordinate cell growth and lineage maintenance following mitosis.…”
Section: Mitotic Bookmarking: a Historical Perspectivementioning
confidence: 99%
“…Ali et al 2008;Bakshi et al 2008;Pande et al 2009;Dey et al 2009;Blobel et al 2009;Ali et al 2010;Zaidi et al 2010;Zhao et al 2011;Ali et al 2012;Kadauke et al 2012;Arampatzi et al 2013;Caravaca et al 2013;Kadauke and Blobel 2013;Zaidi et al 2014;Lake et al 2014;Zaret 2014;Lodhi et al 2014;Wong et al 2014;Lopez-Camacho et al 2014;Lodhi et al 2016;Lerner et al 2016;Festuccia et al 2016). Each of these transcription factors occupy a subset of their target genes during mitosis in their respective lineages.…”
Section: Properties Of Transcription Factors That Function As Mitoticmentioning
confidence: 99%